Microbulk Micromegas in non-flammable mixtures of argon and neon at high pressure. (1st July 2022) - Iguaz, F.J.; Dafni, T.; Canellas, C.; Castel, J.F.; Cebrián, S.; Garza, J.G.; Irastorza, I.G.; Luzón, G.; Mirallas, H.; Ruiz-Chóliz, E.
Abstract: We report on a systematic characterization of microbulk Micromegas readouts in high-pressure Ar+1%iC4 H10 and Ne+2%iC4 H10 mixtures. Experimental data on gain, electron transmission and energy resolution are presented for a wide range of drift and amplification voltages and pressures from 1 bar to 10 bar for the argon mixture and from 5 bar to 10 bar in the neon mixture, in steps of 1 bar. Maximum gains higher than 1.7 × 10 3 (1.7 × 10 4 ) in the argon (neon) mixture are measured for all pressures, without the significant decrease with pressure typically observed in other amplification structures. A competitive energy resolution at 22.1 keV, but with a slight degradation with pressure, is observed: from 10.8% at 1 bar to 15.6% FWHM at 10 bar in Ar+1%iC4 H10 and from 8.3% at 5 bar to 15.0% FWHM at 10 bar in Ne+2%iC4 H10 . The experimental setup, procedure and the results will be presented and discussed in detail. The work is motivated by the TREX-DM experiment, that is operating in the Laboratorio Subterráneo de Canfranc with the mentioned mixtures, although the results may be of interest for other applications of time projection chambers at high pressures.